A bio-wicking system to dehydrate road embankment. (20th September 2018) - Lin, Chuang; Zhang, Xiong
Abstract: Water within pavement layers is a major cause of pavement deteriorations. A small moisture content increment will result in significant reduction in both base course and subgrade resilient behavior and increment in permanent deformation. Conventional drainage systems can drain gravitational water, but not capillary water. An economically feasible, energy saving, and environmentally friendly alternative is required to deal with the excess water induced distresses. Both lab and field tests have proven the effectiveness of a newly developed geotextile with wicking fibers in dealing with such problems as frost heave, thaw weakening, and moisture content induced differential settlement. However, the geotextile is exposed to the open air at the road slope in the original design, raising several potential application concerns, such as ultraviolet degradation, mechanical failure, malfunction due to high suction in the air, and clogging issues. This paper aims at studying the possibility of using a bio-wicking system to address the potential concerns and further reduce the moisture content of base course material for the long run. Two types of tests, elemental-level and full-scale tests, were performed to evaluate the moisture migration in a typical aggregate with 14.5% of fines. Test results indicated that the bio-wicking system successfully addresses the concerns in the original design and is a more effective drainage system to dehydrate a base course compared with the original design.